(3CLfGS GdJLfjSs - (3GdYQGbj, GdMSf Hf eMeO Ydj, J(B803(3g`s
(3ChdgG (B:s
(3cJH CHh efUhQ YHO Gdedc GdKYGdHj Edi GdCejQ UGMH GdLjT fGUQ Hf fGUQ GdOjfhbO SfM ddYHO cJGH Naja GdMLe HYjO GdehGVY aj GdeJTGHg GdPj gh ef CSQGQ GdHdGZI hef CMSf CLfGS GdJLfjSKe Ef gPG GdcJGH eHfj Ydi KdGKI CbSGe aGdbSe GdChd aj GdeJTGHg GdPj jTHg GdJUMjas
(3BNQgG (B:s
(3hOe efjY GdMei eSJeJYG CHOG (B*** (3ef GdfYje HCUaGg hCUaGg , eG Ce hLgI HjJ Gddg eYJeQ (B*** (3jeMh HNWh eWGjGg NWGjGgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 213s
(3eYLe GdeDdajf(B: 2 / 312s
(3cTa GdXfhf(B: 2 / 1135s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdYQhV hGdbhGajs